2019
DOI: 10.1039/c9ra04618f
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogenation of mandelonitrile over a Pd/C catalyst: towards a mechanistic understanding

Abstract: A carbon supported Pd catalyst is used in the liquid phase hydrogenation of the aromatic cyanohydrin mandelonitrile (C6H5CH(OH)CH2CN) to afford the primary amine phenethylamine (C6H5CH2CH2NH2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…205680) was almost exclusively used (sections –). Characterization of this catalyst is reported elsewhere . Because of the large sample size required for INS (≥10 g), a technical-grade 5 wt % Pd/C catalyst was soley used for the INS measurements (Section ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…205680) was almost exclusively used (sections –). Characterization of this catalyst is reported elsewhere . Because of the large sample size required for INS (≥10 g), a technical-grade 5 wt % Pd/C catalyst was soley used for the INS measurements (Section ).…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistic aspects of the single-batch liquid-phase hydrogenation reaction of mandelonitrile (MN) over a carbon-supported palladium catalyst (5 wt % Pd/C) have previously been investigated. , Alongside the desired product, phenethylamine (PEA), the byproduct 2-amino-1-phenylethanol (2-APE) was produced (Scheme ). These prior studies indicated that while the reaction was not completely selective toward phenethylamine ( S = 87%), a closed mass balance was achieved, indicating efficient catalysis under the stated conditions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…tricklebed reactor, bubble column reactor) and stirred tank slurry reactors are usually employed for gas-liquid-solid, three-phase reaction systems. [12][13][14][15][16] However, these traditional reactors possess a few intrinsic problems: (i) the diffusion of reactants and/or products is hindered by limited diffusion channels within the catalytic zone, which result in decreased reaction rates and poor product selectivity. [17][18][19][20] (ii) poor thermal conductivity and mechanical strength in catalyst supports can lead to catalyst sintering and structural degradation during these reactions.…”
Section: Introductionmentioning
confidence: 99%